Foreword (OverHolland, 2017)
OverHolland studies the relationship between architectural interventions and urban transformation, with the focus on towns and cities in Holland. This latest issue of OverHolland takes a closer look at architectural designs, to mark two events in autumn 2013: the publication of the research results of the Renewing city renewal project, an initiative by the architecture firm De Nijl in partnership with Delft University of Technology’s Faculty of Architecture and the KEI knowledge centre for urban renewal (now part of Platform 31); and the DOGMA 11 Projects + 1 exhibition in a temporary pavilion in the grounds of the Faculty of Architecture in Delft.